Foreign Language Reading Anxiety Among Indonesian EFL Senior High School Students - Muhlis, Azhari (ENGLISH FRANCA : Academic Journal of English Language and Education, 2017)
This study aims to investigate foreign language reading anxiety among Indonesian EFL Senior High School students. Thirty twostudents of grade eleven in a senior high school in Bandung were involved as the participants. This study employed a survey research design. The data was collected by two types of questionnaires. The first finding revealed that most of the students perceived anxiety in medium level (71,9% students admitted). The second finding found that there were two major potential factors of foreign language reading anxiety namely text features and personal factors. Under the concept of text features, there are three sources of foreign language reading anxiety including unknown vocabulary (49% students agreed), unfamiliar topic (40% students agreed), and unfamiliar culture (38% students agreed). On the other hand, under the concept of personal factors, there are two sources of foreign language reading anxiety including fear of making errors (39% students agreed), and worry about reading effects (28% students agreed).